Reading Interests and Habits: Their Relationship to the Reading Comprehension of Grade 11 Students - Maribbay, Romel (International Journal of Arts, Sciences and Education, 2022)
Reading remains to be an indispensable tool towards meaningful learning and discovery. One’s reading comprehension skill is pivotal in performing well at school which affects his academic performance. Thus, this study aimed to determine the profile, reading interests and habits and their relationship to the students' level of reading comprehension. It employed a descriptive- correlational research design to establish relationship between the variables. It made use of Molyneux, Paul and Pam Macintyre (2017) survey questionnaire with modifications on the parts where the profile variables are to be elicited as well as a 36-item reading comprehension exercises. The study assessed the reading interests and habits and their relationship to the reading comprehension level of the respondents on finding main idea, finding word meaning through context, understanding sequence, drawing conclusion and making inferences, distinguishing between fact and opinion and summarizing. Students’ reading habits and interests show that most of them enjoy reading sometimes, prefer to read by themselves, like listening to stories or being read to, choose the book themselves and borrow books from their friends, school and classroom library. Likewise, most of them are more likely to read about once a week both for personal and school reasons. The reading materials that they most read are about real life, sports, history and fantasy whereas they least read materials about humor, science and biographies. Moreover, students have a developing reading comprehension level along the six sub-skills tested which made no significant relationship to their reading interests and habits as it translated to their satisfactory academic performance.